Strategi Guru Dalam Mengatasi Kesulitan Membaca Pada Siswa Kelas IV SDS Tarbiyatul Islam Sambas - Isika Chintya Putri; Nuraini; Asyruni Multahada (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The aim of the research is to analyze teacher strategies in teaching students with learning difficulties to introduce reading in learning in class IV at SDS Tarbiyatul Islam Sambas, teacher strategies for teaching students with learning difficulties to write perfect sentences in class IV at SDS Tarbiyatul Islam Sambas; teacher's strategy for teaching spelling letters to students with learning difficulties in class IV students at SDS Tarbiyatul Islam Sambas. This research uses a qualitative approach and a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, conclusions. The research results show that the teacher's strategy in teaching students with learning difficulties to introduce reading in learning in class IV SDS Tarbiyatul Islam Sambas for the 2022-2023 academic year is by using the drill method. The teacher's strategy for teaching students who have difficulty learning to write perfect sentences in class IV at SDS Tarbiyatul Islam Sambas for the 2022-2023 academic year is that students must have a special writing book to practice writing neatly. Apart from that, the teacher also provides evaluations to students and provides notes at home to see student activity. in the classroom. The teacher's strategy for teaching spelling letters to students with learning difficulties in class IV students at SDS Tarbiyatul Islam Sambas for the 2022-2023 academic year is that first the teacher uses the drill method during the learning process, the second uses learning media such as class IV textbooks and notebooks and the third gives assignments to students